Development of Video Tutorial-Based Learning Media on Reflexiology Treatment Courses - Cinthia, Deby; Yuliana, Yuliana; Rahmiati, Rahmiati; Effendi, Hansi (Al Makki Publisher, 2023)
In the reflexology course, there are certain stages of treatment, so that students do not understand reflexology treatment if the explanation is only through writing, pictures and practice times, resulting in a lack of understanding of students about the stages of reflexology treatment as a whole. The learning media designed is using video tutorial-based learning media. Video tutorial is one of the media that uses a presentation display in the form of a video that shows the steps of work. The development of learning media based on video tutorials is carried out with 4-D development, namely the development of a model consisting of four stages, including: define, design, development and dissemination. The purpose of developing this learning media is to produce a Reflexology Treatment video tutorial that has valid, practical and effective criteria. From the results of the recapitulation of student learning outcomes with an average gain score of 0.809, that is in the high category. So seen from the cognitive learning outcomes of students who take courses using video tutorials, it shows that the video tutorial-based learning media developed by researchers is effective in improving student learning outcomes.